Access to oral health care for undocumented migrants: Perspectives of actors involved in a voluntary dental network in the Netherlands. Issue 4 (20th December 2020) - van Midde, Myrthe; Hesse, Iris; van der Heijden, Geert JMG; Duijster, Denise; van Elteren, Marianne; Kroesen, Margreet; Agyemang, Charles; Beune, Erik
Abstract: Objective: Undocumented migrants in Europe face multiple barriers in access to oral health care. This study aimed to explore the accessibility of a voluntary dental network providing dental treatments to undocumented migrants in the Netherlands, from the perspectives of patients, dentists and staff members of nongovernmental organizations involved. Methods: This qualitative study used semi‐structured interviews (n = 21) with undocumented migrants (n = 12), dentists (n = 7) and staff members of nongovernmental organizations (n = 2) during the implementation of a voluntary dental network. Interviews were analysed using a framework analysis method. Results: As a temporary answer to problems in access to oral health for undocumented migrants, the voluntary dental network targeted initial barriers to dental care. Main challenges within the network were conflicting expectations and perceived treatment outcomes by patients, dentist and NGO staff members, limited financial resources, logistic and communication barriers and an increasing administrative burden. Furthermore, feelings of compassion for and trust of the patient affected the ethics of the professional relationship and influenced treatment decisions of dentists. Conclusion: Through the implementation of a voluntary dental network, treatments could be provided to undocumented migrants as a temporary solution. However, the voluntary nature of dental care in the network resulted in a fragmented provision of oral health care among undocumented migrants. To reduce inequalities in oral health on the long term, systemic barriers in access to oral health care need to be addressed.